Evolution of Sectoral Energy Consumption in India - Sahoo, Janmejay (Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
The increasing dependence on energy plays a significant role in shaping out our future energy demands and economic growth. The main concerns regarding this approach are related to the limited availability of energy sources and their impact on global climatic conditions. These impacts are further exaggerated due to the lack of a coordinated approach towards reducing energy consumption for a sustainable alternative. The article focuses on the end-use energy consumers which are primarily agricultural, transportation, industry, residential and commercial sectors and how the use of technology and urbanization has impacted them. Using the contribution of these sectors and the population growth, alternative future scenarios were developed and compared, where the advantages of an energy-efficiency approach was exhibited. At an urban level, these sectors were associated to different land uses and their potential to improve energy efficiency was explained using various techniques and indicators. One of the primary goals of this article was to explain the methodologies to achieve energy efficiency in communities, which was explained using the role of comprehensive technologies like GIS and integrated approaches under urban planning. Case studies of Bangalore and Massachusetts were elaborated to comprehend such initiatives at a city scale and how they can be implemented in reality. Exploring these questions sets a course for informing local land use decisions that impact energy consumption.